Prostate cancer-associated mutations in speckle-type POZ protein (SPOP) regulate steroid receptor coactivator 3 protein turnover - Geng, Chuandong; He, Bin; Xu, Limei; Barbieri, Christopher E.; Eedunuri, Vijay Kumar; Chew, Sue Anne; Zimmermann, Martin; Bond, Richard; Shou, John; Li, Chao; Blattner, Mirjam; Lonard, David M.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
The p160 steroid receptor coactivators (SRCs) SRC-1, SRC-2 [nuclear receptor coactivator (NCOA)2], and SRC-3 [amplified in breast cancer 1 (AIB1)/NCOA3] are key pleiotropic “master regulators” of transcription factor activity necessary for cancer cell proliferation, survival, metabolism, and metastasis. SRC overexpression and overactivation occur in numerous human cancers and are associated with poor clinical outcomes and resistance to therapy. In prostate cancer (PC), the p160 SRCs play critical roles in androgen receptor transcriptional activity, cell proliferation, and resistance to androgen deprivation therapy. We recently demonstrated that the E3 ubiquitin ligase adaptor speckle-type poxvirus and zinc finger (POZ) domain protein (SPOP) interacts directly with SRC-3 and promotes its cullin 3-dependent ubiquitination and proteolysis in breast cancer, thus functioning as a potential tumor suppressor. Interestingly, somatic heterozygous missense mutations in the SPOP substrate-binding cleft recently were identified in up to 15% of human PCs (making SPOP the gene most commonly affected by nonsynonymous point mutations in PC), but their contribution to PC pathophysiology remains unknown. We now report that PC-associated SPOP mutants cannot interact with SRC-3 protein or promote its ubiquitination and degradation. Our data suggest that wild-type SPOP plays a critical tumor suppressor role in PC cells, promoting the turnover of SRC-3 protein and suppressing androgen receptor transcriptional activity. This tumor suppressor effect is abrogated by the PC-associated SPOP mutations. These studies provide a possible explanation for the role of SPOP mutations in PC, and highlight the potential of SRC-3 as a therapeutic target in PC.